Bacillus sp. QSI-1 Modulate Quorum Sensing Signals Reduce Aeromonas hydrophila Level and Alter Gut Microbial Community Structure in Fish - Zhou, Shuxin; Zhang, An; Yin, Hongping; Chu, Weihua (Frontiers in Cellular and Infection Microbiology, 2016)
Quorum sensing (QS) is a cell density dependent process that enables bacteria to communicate with each other based on the production, secretion and sensing of the auto-inducer molecules and then subsequently regulate virulence associated gene expression. Interrupting quorum sensing may represent a novel alternative approach to combat bacterial pathogen. Several bacteria can produce quorum quenching (QQ) enzymes. However, the role of QQ bacteria in shaping the microbiota and the level of N-acyl-homoserine lactones (AHLs, a prevalent type of QS molecules) producing bacteria remains largely unknown. The objective of this study was to examine the presence of AHLs in the fish intestine and investigate the modulation of gut microbiota and its effect on Aeromonas hydrophila level by a QQ enzyme producing probiotic Bacillus sp.QSI-1. AHLs were found in fish gut content and were confirmed in Aeromonas species using Chromobacterium violaceum CV026 and Agrobacterium tumefaciens AT 136 (pZLR4) as reporter strains. We demonstrated that the composition of fish gut microbiota was affected by quenching bacteria QSI-1, and the percentage of A. hydrophila was decreased significantly. Taken together, these results provide valuable insights into QQ enzyme producing probiotics can modulate the microbiota structure and decrease the percentage of AHL-producing pathogenic bacteria in the gut. These data strongly suggest that QQ probiotics may serve as non-antibiotic feed additive in aquaculture to control bacterial diseases.